Les mobilisations des victimes de pesticides ont-elles modifié les pratiques des viticulteurs languedociens ? - Christian Nicourt (VertigO)
The article proposes to consider a possible inflection of conceptions of winegrowers pains they suffer when applying pesticides. Now victims of pesticides have formed an association and have promoted the recognition of occupational diseases. This is a break. Among winegrowers investigated a decade ago, this conception change seems however limited. Indeed, contemporary shifts in the profession seem rather linked to the new crisis experienced by growers, forcing their work, especially into individualization. Their use of pesticides did not vary much. They do not notice abnormal mortalities among their colleagues, and the pains or diseases they suffer, while their individual use of pesticides, does not seem to be an alert for them. They still deny its scope by dissolving them in the wide category of work daily pains. For employers, perform treatments now becomes legally risky. It is mainly local residents, or institutions, rather than wine growers that now challenge the use of pesticides. While local authorities are concerned about quality of drinking water, the market is like a judge examining only incriminating facts. The demand for organic wines is growing, while cellarmen customer’s even oenologists challenge winegrowers on their pesticide use. Despite these inflections, the denial of winegrowers on the consequences of pains they suffer still seems mostly their only possible strategy.